Cleaning lateral morphological features of the root canal: the role of streaming and cavitation. (31st July 2017) - Robinson, J. P.; Macedo, R. G.; Verhaagen, B.; Versluis, M.; Cooper, P. R.; van der Sluis, L. W. M.; Walmsley, A. D.
Abstract: Aim: To investigate the effects of ultrasonic activation file type, lateral canal location and irrigant on the removal of a biofilm‐mimicking hydrogel from a fabricated lateral canal. Additionally, the amount of cavitation and streaming was quantified for these parameters. Methodology: An intracanal sonochemical dosimetry method was used to quantify the cavitation generated by an IrriSafe 25 mm length, size 25 file inside a root canal model filled with filtered degassed/saturated water or three different concentrations of NaOCl. Removal of a hydrogel, demonstrated previously to be an appropriate biofilm mimic, was recorded to measure the lateral canal cleaning rate from two different instruments (IrriSafe 25 mm length, size 25 and K 21 mm length, size 15) activated with a P5 Suprasson (Satelec) at power P8.5 in degassed/saturated water or NaOCl. Removal rates were compared for significant differences using nonparametric Kruskal–Wallis and/or Mann–Whitney U ‐tests. Streaming was measured using high‐speed particle imaging velocimetry at 250 kfps, analysing both the oscillatory and steady flow inside the lateral canals. Results: There was no significant difference in amount of cavitation between tap water and oversaturated water ( P = 0.538), although more cavitation was observed than in degassed water. The highest cavitation signal was generated with NaOCl solutions (1.0%, 4.5%, 9.0%) ( P < 0.007) and increased with concentration ( P < 0.014). The IrriSafe file outperformed significantly the K ‐file in removing hydrogel ( P < 0.05). Up to 64% of the total hydrogel volume was removed after 20 s. The IrriSafe file typically outperformed the K ‐file in generating streaming. The oscillatory velocities were higher inside the lateral canal 3 mm compared to 6 mm from WL and were higher for NaOCl than for saturated water, which in turn was higher than for degassed water. Conclusions: Measurements of cavitation and acoustic streaming have provided insight into their contribution to cleaning. Significant differences in cleaning, cavitation and streaming were found depending on the file type and size, lateral canal location and irrigant used. In general, the IrriSafe file outperformed the K ‐file, and NaOCl performed better than the other irrigants tested. The cavitation and streaming measurements revealed that both contributed to hydrogel removal and both play a significant role in root canal cleaning.